2004
DOI: 10.1074/jbc.m312927200
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Gene fad158, Having a Transmembrane Domain and Leucine-rich Repeat, Stimulates Adipocyte Differentiation

Abstract: Adipocyte differentiation is known to be regulated by a complex array of genes known as master regulators. Using a subtraction method, we previously isolated 102 genes that are expressed in the early stage of adipocyte differentiation. One of these genes named fad158 (factor for adipocyte differentiation 158) seems to be a novel gene, since there is no significantly similar gene listed in databases. Both mouse and human fad158 encode 803 amino acids and contain 4 transmembrane regions and 8 leucine-rich repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
(50 reference statements)
1
36
0
Order By: Relevance
“…LRRC8 proteins also lack a signal peptide and are subjected to glycosylation, at least in the case of LRRC8A and D, the two most widely expressed paralogues [30]. Moreover, LRRC8A and D have been found at the surface of the cell [30] and LRRC8C at the ER [3].…”
Section: Subcellular Localisation Of Lrrc8 Proteins Resembles That Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…LRRC8 proteins also lack a signal peptide and are subjected to glycosylation, at least in the case of LRRC8A and D, the two most widely expressed paralogues [30]. Moreover, LRRC8A and D have been found at the surface of the cell [30] and LRRC8C at the ER [3].…”
Section: Subcellular Localisation Of Lrrc8 Proteins Resembles That Ofmentioning
confidence: 99%
“…immune synapses) would help to clarify whether they are involved in direct or indirect (paracrine) cell-cell communi- cation. Considering the relevant role of pannexins at the ER [61] and that LRRC8C has already been detected at that particular location [3], it would also be important to determine the function of LRRC8 proteins in this organelle. Characterisation of protein-protein interactions, transient or stable, with proteins that participate in signalling cascades and/or cell-cell junctions will also throw light on the function of these proteins.…”
Section: Next Steps In Deciphering the Functions Of Lrrc8 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that FAD158 localized to the endoplasmic reticulum (ER) through its four N-terminal transmembrane regions. 5) Alteration of the actin cytoskeleton is necessary for early adipocyte differentiation. 25) In addition, Dadke and Chernoff reported that protein-tyrosine phosphatase 1B (PTPIB) localized to the ER, and activated Src, thereby initiating the activation of a Rac-dependent pathway leading to cytoskeletal remodeling.…”
Section: -7)mentioning
confidence: 99%
“…We previously generated stable transformants expressing antisense-TCL/TC10bL and fad158, and described that inhibition of the expression of TCL/TC10bL and fad158 impaired adipogenesis. 4,5) Moreover, using an RNAi method, we found that the knockdown of fad104 expression reduced the ability of 3T3-L1 cells to differentiate. 6) In addition, RGS2-expressing NIH-3T3 cells converted to adipocytes.…”
mentioning
confidence: 99%